ANALISIS SWOT DALAM PENERAPAN PROGRAM PENANGANAN ANAK JALANAN MELALUI POLA PEMBINAAN TERPADU BERBASIS KEMITRAAN DI KOTA PADANG - Mesi Aria Putri; Zikri Alhadi (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
The purpose of this study is to analyze a program using a SWOT analysis (strengths, weaknesses, opportunities, and threats) in the street children handling program through a partnership-based integrated coaching pattern in the city of Padang. This program aims to provide physical, mental and spiritual training for street children in an integrated manner so that these children are no longer active on the streets, and make the city of Padang free from street children. This research is a qualitative research using descriptive method. The data was collected by means of interviews and documentation studies, interview guides with several prepared questions. Data aids that the author uses cameras, cellphones, and recording devices. Selection of informants by purposive sampling. To test the validity of the data by means of triangulation of sources. From the research results it can be revealed that the strength of this program lies in sufficient human resources, the weakness of this program is the lack of budget which has an impact on the lack of program implementation and the unequal coaching of the netted children. Opportunities from this program are MOU with several stakeholders and involve Battalion 133 / Yudha Sakti. The threat from this program is that there are parents or families of street children who do not give permission to participate in integrated coaching.